PERAN MANAJEMEN PENDIDIKAN NONFORMAL BERBASIS MASYARAKAT SEBAGAI UPAYA PENINGKATA SUMBER DAYA MANUSIA DI INDONESIA - Muslim, Abd. Qadir; Sedana Suci, I Gede (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
Human development is compulsory by means of an education process, one of which is the educational process at non-formal educational institutions. Non-formal education is an interesting topic, because the education process is community-based, that is, its management contains principles from the community, with the community, and towards the community. This study aims to examine, identify and understand the role of community-based non-formal education management as an effort to increase human resources. This study uses a qualitative approach with library research methods, namely examining, analyzing and developing theories from research results related to the theme of the role of community-based non-formal education management as a form of creating human beings who have capabilities, competencies and character according to the needs of society and the times.The results showed that in community-based education, the community as instructors and learning citizens were the determining factors for the success of non-formal education. Non-formal education which is considered as a complement to and a substitute for formal education has a wider variety of materials being taught. Non-formal education teaches things related to the surrounding environment, and is formed and managed by the community with guidance from the government. In Indonesia, this type of non-formal education is held independently or with government assistance. However, there are still many institutions that have not received attention in the form of accreditation from the government. Even though there are many results that prove that non-formal education graduates absorb more workers because of skills related to current social conditions.